Plaque-like dermatofibroma: A case report and review of the literature - Sinan Nane; Aslı Bilgiç; Cumhur İbrahim Başsorgun; Erkan Alpsoy (Turkderm Turkish Archives of Dermatology and Venereology, 2022)
Dermatofibromas are common skin tumors although there are some different clinical forms, which are seen rarely. Giant dermatofibromas are benign, pedunculated lesions that are larger than 5 cm with typical dermatofibroma histopathologic features. Typically, plaque-like dermatofibromas are considered a subtype of giant dermatofibromas without a pedicule. Here, we aimed to report a case of plaque-like dermatofibroma seen in a 5-year-old girl due to its rarity and to review this clinical picture together with all the cases in the literature.